United States and European Union Auditor Independence Regulation Implications for Regulators and Auditing Practice - Strohm, Christiane. (Forschungsreihe Rechnungslegung und Steuern, 2006)
In recent years, the Sarbanes-Oxley-Act has received international attention unlike few other laws. The rules presented in this act take influence on business practice and dominate the ongoing discussion on business constitution in the USA as well as in Europe. Christiane Strohm investigates the effects of the Sarbanes-Oxley-Act and the revised 8th EU-Directive on auditing. The results of her first experiment indicate that there is a difference in the communication and safeguarding effects of a regulation, depending on the precision of its wording. Findings of her second experiment show that safeguarding effects also depend on auditors' monetary incentives and on perceived costs of litigation. The author also tests the effectiveness of a transparency report which is proposed by the European Union. The most important safeguards (policies and procedures) are perceived to be quality assurance, internal quality controls and independence practice and compliance.